2005
DOI: 10.1086/497339
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Costs of Diarrheal Disease and Estimates of the Cost‐Effectiveness of Rotavirus Vaccination in Vietnam

Abstract: Vaccination can effectively reduce the disease burden and health care costs of rotavirus-specific diarrhea in Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
124
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(134 citation statements)
references
References 9 publications
8
124
0
2
Order By: Relevance
“…The total direct costs of diarrhea in children under the age of 5 years in Albania are higher compared to that of other developing countries. For example, Fischer et al Reported that the total direct costs of diarrhea in children younger than 5 years in Vietnam were approximately $4 million in 2004 [7], but the population of Vietnam is around 25 times higher than that of Albania. In Uzbekistan, the hospitalization cost of a diarrhea case was about $77.8 in 2004 [13] whereas we report an average hospitalization cost of $229 per case.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The total direct costs of diarrhea in children under the age of 5 years in Albania are higher compared to that of other developing countries. For example, Fischer et al Reported that the total direct costs of diarrhea in children younger than 5 years in Vietnam were approximately $4 million in 2004 [7], but the population of Vietnam is around 25 times higher than that of Albania. In Uzbekistan, the hospitalization cost of a diarrhea case was about $77.8 in 2004 [13] whereas we report an average hospitalization cost of $229 per case.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested in the literature, rotavirus is a very common cause of severe diarrhea and hospitalization for children under age of five in developed [12,14,16] and developing countries [4]. Numerous studies have shown that rotavirus immunization programs might be cost-effective, even though many aspects have to be taken into consideration such as morbidity and mortality rates due to rotavirus and vaccine price [7,12,13,15]. Besides the actual costs of diarrhea, these very important aspects related to rotavirus immunization should be investigated through carefully designed future studies, in order to help the decision makers to opt for a vaccination program or other potential interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies provided incremental costs per DALY averted for Vietnam; for a full course vaccination cost of $10 (€8), the estimated ICERs were $91 (€70) in one study 69 and $550 (€420) in another, 70 from a TPP perspective. The study by Podewils et al 71 showed that cost-effectiveness at different prices is highly dependent upon the level of income of studied countries.…”
Section: Overview Of Studiesmentioning
confidence: 99%